PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KAREKTER DISIPLIN DAN TANGGUNG SISWA DI MTS MIFTAHUL ULUM TANJUNGARUM SUKOREJO PASURUAN - Muhammad Alfan Salim; Ahmad Subekti; Moh. Muslim (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The teacher has an important role in the role of the teacher (PAI) in efforts to form the character of students' discipline and responsibility at MTs Miftahul Ulum Tanjungarum. The formation of this character itself has the aim good behavior in this case has noble character and family relations with the community or social sphere. This study is motivated by our nation's declining discipline in terms of punctuality, and also the problem of student disorder in learning which results in failure to achieve good grades. In addition, the current sense of human responsibility towards the environment and nature that does not improve is the background of this research. This has led researchers to carry out research at MTs Miftahul Ulum Tanjungarum which has attempted to make Islamic teachings a foundation in educating students including this character of discipline and responsibility through school activities and programs.